Merekam Permasalahan Sosial dalam Novel Brianna dan Bottomwise Karya Andrea Hirata: Kajian Sosiologi Sastra - Siti Maesaroh; Iffah Fauziah Rahardy (Universitas Palangka Raya, 2025)
Social issues are one of the most interesting themes to be raised in a literary work. One novel that raises social issues is Brianna and Bottomwise by Andrea Hirata. This detective-themed novel addresses various social issues in society. This study, entitled “Social Issues in Andrea Hirata's Brianna and Bottomwise,” aims to describe various social issues in Andrea Hirata's Brianna and Bottomwise. The research method used is descriptive qualitative. Data collection was carried out using a literature study method on the novel. The collected data was analyzed using literary sociology theory. The results of this study describe various problems found in Andrea Hirata's novel Brianna and Bottomwise, including verbal and physical abuse, theft, family disorganization, gambling, poverty, cultural shifts, and drug abuse. The findings of this study are expected to provide additional information related to various social issues that can occur in society.This research is expected to provide deeper insight into the depiction of social problems in literary works and provide useful information regarding social problems that often occur in society, as well as how literary works can be a reflection and criticism of existing social conditions.